The Influence of Human Resources Competence in the Field of Taxation on Compliance and Effectiveness of Fulfillment of Tax Obligations: A Literature Study - Lina Mariana; Sariana Damis; Hernianti Harun; Nur Sandi Marsuni (Jurnal Riset Perpajakan: Amnesty, 2025)
This study aims to systematically examine the role of Human Resources (HR) competence in the field of taxation on compliance and effectiveness of tax obligations, both in the private and public sectors. This study was conducted through a literature review method by examining various scientific journals, articles, and relevant previous research results. The main focus of the study is on the dimensions of HR competence such as technical knowledge of taxation, training and certification (eg tax brevet), and professional experience in managing tax obligations. The results of the study indicate that HR with high competence in the field of taxation tend to be able to significantly increase taxpayer tax compliance, both in terms of formal (reporting) and substantive (payment and planning). In addition, strengthening HR capacity has been proven to minimize the risk of administrative errors, reduce potential sanctions, and support more efficient and accountable tax planning strategies. Adequate tax literacy also encourages increased communication between companies and tax authorities, thereby creating a healthier compliance climate. This study concludes that HR competence is one of the main pillars in modern tax management and must be a priority in the development of tax policies and organizational governance strategies. The findings of this literature review are expected to be a reference for policy makers, academics, and practitioners to develop a more structured and sustainable HR strengthening program in the taxation sector.